The design of non thermal plasma exhaust treatment for NOx removal in diesel engine vehicles [electronic resource] - Nur Zarith Sofiah Mohamed Azhar, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2010